Utility of acoustic location technology for studying avian dawn choruses: Social dynamics of male black-capped chickadees - Foote, Jennifer; Mennill, Daniel; Ratcliffe, Laurene (Canadian Acoustics, 2006)
The use of acoustic location technology for studying the avian dawn choruses are discussed. The social dynamics hypothesis predicts that social relationships among males will be reflected in their dawn chorusing interactions. The acoustic location systems can be used to locate singers in space and time and monitor the content of vocal interactions of multiple individuals. It was tested whether black-capped chickadee choruses could be reconstructed from multi-channel ALS recordings. If choruses are successfully reconstructed then acoustic location can be used to examine content and function of male dawn choruses. A multi-channel data acquisition card was used to digitize microphone input. GPS coordinates of microphones and nests were taken using a Trimble GPS system. From the ALS recordings, it can be determined if males interact at dawn using frequency matching and whether interactions reflect male social dynamics.